Analysis of Students Mathematical Reasoning Ability in Solving Algebra Word Problems in terms of Learning Styles - Farah, Ainul; Zuhri, Zainullah (Universitas Negeri Surabaya, 2022)
This study aims to describe students' mathematical reasoning abilities in solving algebra word problems in terms of learning styles. This type of research is descriptive qualitative research. The research subjects were class VII A students of SMPN 1 Pasrepan for the 2022/2023 academic year. The subjects in this study were 2 students with a visual learning style, 2 students with an auditory learning style, and 2 students with a kinesthetic learning style. Data collection techniques in this study were learning style questionnaires, mathematical reasoning ability tests, and interviews. Triangulation in this study uses triangulation techniques. The results of this study indicate that subjects with a visual learning style have high mathematical reasoning abilities with a percentage of 78.75%, subjects with an auditory learning style have high mathematical reasoning abilities with a percentage of 93.75%, and subjects with a kinesthetic learning style have reasoning abilities moderate mathematics with a percentage of 60%.